PENGARUH PROFITABILITAS, STRUKTUR MODAL, LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN MODERASI GENDER DIVERSITY DAN INFLASI - Gita Delviana Deli; Sunarto Sunarto (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study addresses the inconsistency of prior findings on how profitability, capital structure, and liquidity affect firm value in energy and mining companies, particularly under governance and macroeconomic pressures. The purpose of this study is to examine the effects of Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) on Tobin's Q, and to test the moderating roles of gender diversity and inflation. This quantitative study uses secondary data from annual financial statements and annual reports of energy and mining companies listed on the Indonesia Stock Exchange during 2017-2024. The sample was selected using purposive sampling and produced 100 valid firm-year observations. Data were analyzed using Moderated Regression Analysis (MRA) with SPSS. The results show that ROE, DER, CR, gender diversity, and inflation have negative and significant effects on firm value. Gender diversity weakens the negative effect of DER and strengthens the effect of CR on firm value, while inflation only strengthens the relationship between CR and firm value. The novelty of this study lies in the simultaneous use of gender diversity and inflation as quasi-moderators in a capital-intensive and macro-sensitive sector. The limitation of this study is that it uses a limited sectoral sample, a national inflation proxy, and an OLS-based MRA model that still indicates positive autocorrelation.